OH-2 Whatsapp Messanger As a Communication, Coordination And Evaluation Media In Rabies Control Program In Bengkalis District - Hani M Mardan; Abdul Muthalib; Rini Deswita; Dewi Anggreini (Hemera Zoa, 2018)
INTRODUCTIONZoonotic control program can not only be done by one sector only, but must involve related sectors so that handling can be done comprehensively. Since 2016 Bengkalis Disctrict has been chosen as one of project area of One Health on prevention and control of targeted emerging infectious diseases and targeted zoonotic, especially rabies. 3 steps of training have been conducted for public health officers, animal health officer and wildlife health officer who served in Bengkalis District.The absence of an information system on rabies-transmitted animal bites cases that can be accesed by officers from these three sectors has hampered the communication process which is the first step in implementing rabies prevention and control activities. Therefore we need a media that can bridge officers from the animal health, public health and wildlife health sector in communicating related cases of rabies-transmitted animal bites. As one of the output of One Health project, a whatsapp messanger grup, named “One Health Riau” have been created for all the field officers from the three sector to help them to communicate.This study aims to provide an overview of the use of whatsapp messenger to communicate, coordinate and also to evaluate field officers in the handling of rabies-transmitted animal bite cases in Bengkalis District during March to May 2018.